COMPETENCE OF TEACHERS IN THE PROCESS OF DIGITALIZATION IN HIGHER EDUCATION - Milena , Milena Filipova; Yuleva - Chuchulayna, Radostina Emilova (Revista Inclusiones, 2021)
The big changes that are occurring today in the field of digital technologies and digitalization affect all spheres of life, including higher education. People’s knowledge and competencies are built from an early age, and university professors enrich and reinforce this. Changes affecting every aspect of life, including those related to "Covid 19" lead to the acceleration of the digitalization process in education. This in turn creates the need to improve existing skills, knowledge and competences. The changes in the technologies and economic situation of Bulgaria place new requirements in terms of the skills and individual competencies of teachers in higher education. The main objective of this development is aimed at identifying the specificities of the digitalization process in higher education and the necessary competences of teachers. The main research methods used in the development are contingent analysis, method of comparison, method of analysis and synthesis, intuitive and systematic approach.